Examining hand dominance using dynamometric grip strength testing as evidence for overwork weakness in Charcot–Marie–Tooth disease: a systematic review and meta-analysis. Issue 3 (September 2016) - Roberts-Clarke, Daniel; Fornusek, Che; Fiatarone Singh, Maria A.; Burns, Joshua; Hackett, Daniel A.
Abstract : This systematic review with a meta-analysis of studies was carried out to evaluate the potential of overwork weakness on the basis of grip strength of dominant and nondominant hands in individuals with Charcot–Marie–Tooth disease (CMT). Numerous electronic databases were searched from the earliest records to February 2016. Studies of any design including participants older than 18 years of age with a confirmed diagnosis of CMT that measured grip strength of both hands using dynamometric testing were eligible for inclusion. Of 12 593 articles identified following removal of duplicates, five articles fulfilled the criteria. A total of 166 participants, mostly with CMT1 or CMT2, were described from the studies included. Hand and finger pinch grip strength for the dominant compared with the nondominant hand was not statistically different. There is no definitive evidence that preferential use of the dominant hand in CMT impairs function relative to the nondominant hand. Thus, robust exercise trials of progressive resistance training are needed to understand the extent of adaptations possible and provide evidence of the safety of such regimens.